Much more than you expected: The non-DHFR-mediated effects of methotrexate - Sramek, Martin; Neradil, Jakub; Veselska, Renata (Biochimica et biophysica acta. General subjects, 2017)
For decades, methotrexate (MTX; amethopterin) has been known as an antifolate inhibitor of dihydrofolate reductase (DHFR), and it is widely used for the treatment of various malignancies and autoimmune diseases. Although the inclusion of MTX in various therapeutic regimens is based on its ability to inhibit DHFR and consequently to suppress the synthesis of pyrimidine and purine precursors, recent studies have shown that MTX is also able to target other intracellular pathways that are independent of folate metabolism. The main aim of this review is to summarize the most important, up-to-date findings of studies regarding the non-DHFR-mediated mechanisms of MTX action. The effectiveness of MTX is undoubtedly caused by its capability to affect various intracellular pathways at many levels. Although the most important therapeutic mechanism of MTX is strongly based on the inhibition of DHFR, many other effects of this compound have been described and new studies bring new insights into the pharmacology of MTX every year. Identification of these new targets for MTX is especially important for a better understanding of MTX action in new protocols of combination therapy. •Methotrexate is widely used as an inhibitor of dihydrofolate reductase for decades.•Methotrexate affects also pathways that are independent of folate metabolism.•The diverse effects of methotrexate are apparently concentration-dependent.•Identification of these new targets is important for combination therapy.